Continuidade do cuidado às crianças pré-termo egressas da Unidade de Terapia Intensiva Neonatal : perspectiva da família - Silva, Emanuelly Ferreira Lima (2021)
Preterm newborns commonly have weaknesses that lead to the need for admission to the Neonatal Intensive Care Unit, where they will receive support for their vital functions. When they are discharged and go home, the family undergoes a reorganization of their daily lives to meet their needs and experiences a search for care in various health services, in order to ensure continuity of care after discharge. However, they face difficulties such as the disarticulation of services, access difficulties due to the distance traveled to the health units, as well as the time spent on commuting, lack of family support, among others. Due to the aforementioned challenges and in an attempt to meet the child's health needs, the family seeks and manages care, according to their own illness experiences. This fact points to the need to recognize the family and its role in the care of preterm infants discharged from intensive care units. This study aims to understand the continuity of care for children born prematurely discharged from a neonatal intensive care unit, from the perspective of the family. This is an exploratory study with a qualitative approach, carried out with 16 relatives of preterm newborns with gestational age less than 32 weeks and who were admitted to a neonatal intensive care unit in Cuiabá, Mato Grosso. Data collection was carried out at the family's home through semi-structured interviews, lasting 80 minutes on average and recorded in audio. The audio of the interviews was transcribed in full and submitted to thematic content analysis. This study is an excerpt from the matrix research project entitled “The continuity of care for prematurely born children discharged from the Neonatal ICU: search for the construction of integrality”, approved by the Ethics Committee under the embodied opinion number 2.788.928. The results were presented in two manuscripts: Experience of the family in the care of preterm newborns and Continuity of care for preterm newborns: family experiences. This research made it possible to approach the reality of families regarding the continuity of care for preterm infants discharged from the Neonatal ICU in the context of the capital of the state of Mato Grosso. From the families' reports, elements that make up the three dimensions of continuity of care, informational, relational and management are evidenced. In the reality studied, there is still a discontinuity of care for preterm infants who have been discharged from the Neonatal ICU, despite the public policies already implemented in the national context for its effectiveness and improvement in the care provided to the child after discharge. There are weaknesses in the articulation between hospital care and primary care, and the lack of information highlights a significant failure in the neonatal care provided. In this study, the family is shown as the protagonist of care for the child discharged from the Neonatal ICU, reinforcing the importance of attention to the family after discharge and the creation of strategies that include it in care, since continuity depends largely on their understanding and collaboration in preterm care. We endorse the importance of knowing the experience of families about the continuity of care for preterm infants discharged from the Neonatal ICU in order to guide the planning of health actions, with a view to ensuring continuity and improving the care offered to this public.